Multilocus identification of Colletotrichum species associated with papaya anthracnose - Ruiz Campos, Catalina del Carmen (2022)
Introduction. Anthracnose caused by Colletotrichum spp., is the main postharvest disease of papaya worldwide. Molecular approaches have allowed the identification of new species of the genus associated with tropical fruits anthracnose in different countries. Objective. To identify, by morphological and molecular techniques, the Colletotrichum species associated with papaya anthracnose in Costa Rica. Materials and methods. During 2014 and 2015, 129 Colletotrichum spp. monosporic isolates were established from papaya fruits exhibiting anthracnose symptoms, collected in Parrita, San Carlos, and Guácimo, Costa Rica. All isolates were characterized by colony morphology and PCR with taxon- specific primers for the species C. gloeosporioides s.l. , C. acutatum s.l. , respectively, and with species-specific primers for C. magnum and C. truncatum . Species identification was confirmed by multilocus analysis, base on the partial sequence of the actin(ACT), β-tubulin (TUB2), glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and chitin synthase 1 (CHS) genes and the ITS region. The phylogenetic analysis was based on the criteria of Maximum Likelihood and Bayesian analysis. Results. Six species were identified, C. fructicola , C. tropicale , C. theobromicola of the C. gloeosporioides species complex, C. simmondsii of the C. acutatum species complex, C. truncatum , and C. magnum s.l. , being the latter the dominant species. Temperatures above 18 °C allowed the development of five species, C. theobromicola , C. fructicola , C. tropicale , and C. magnum s.l. , which showed accelerated growth, while C. simmondsii had slow growth. Conclusion. The multilocus analysis was able to identify species belonging to the C. gloeosporioides and C. acutatum complexes. This is the first report of C. fructicola , C. tropicale , C. theobromicola , and C. simmondsii associated with anthracnose of papaya fruits in Costa Rica.